2010
DOI: 10.1074/jbc.m110.121129
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorylation and Activation of Androgen Receptor by Aurora-A

Abstract: Aurora-A kinase is frequently overexpressed/activated in various types of human malignancy, including prostate cancer. In this study, we demonstrate elevated levels of Aurora-A in androgen-refractory LNCaP-RF but not androgen-sensitive LNCaP cells, which prompted us to examine whether Aurora-A regulates the androgen receptor (AR) and whether elevated Aurora-A is involved in androgen-independent cell growth. We show that ectopic expression of Aurora-A induces AR transactivation activity in the presence and abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 45 publications
(56 reference statements)
2
20
0
Order By: Relevance
“…Intriguingly, in the AVPC, AURKA nuclear expression correlated with AR expression. Indeed, the interactome of AURKA is large(37) and includes cell cycle and transcriptional regulators such as AR(38), Tp53(39), MYC(40), and BRCA1(41). In turn, Tp53 mutants increase AURKA expression and cooperate with AURKA in the induction of genomic instability(42) (also a likely feature of the AVPC suggested by the high rate of CNA observed) and in the regulation of DNA damage repair(43).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, in the AVPC, AURKA nuclear expression correlated with AR expression. Indeed, the interactome of AURKA is large(37) and includes cell cycle and transcriptional regulators such as AR(38), Tp53(39), MYC(40), and BRCA1(41). In turn, Tp53 mutants increase AURKA expression and cooperate with AURKA in the induction of genomic instability(42) (also a likely feature of the AVPC suggested by the high rate of CNA observed) and in the regulation of DNA damage repair(43).…”
Section: Discussionmentioning
confidence: 99%
“…95). There are many examples of serine/threonine and tyrosine kinases implicated in AR phosphorylation and amongst the most interesting are Aurora kinase A (Aurora-A), 96 cyclin-dependent kinase 1 (Cdk1), 97,98 PIM1 kinase, 99 Src and Ack1; 100102 all of these are targets of small molecule inhibitors in clinical development.…”
Section: Mechanisms Of Maintained Ar Activity In Crpcmentioning
confidence: 99%
“…In vitro kinase assays showed that the AR can be phosphorylated by the Serine/Threonine kinase Aurora-A (Shu et al 2010). Sequence analysis predicted that the N-terminal T282 and S293 were two potential Aurora-A phosphorylation sites.…”
Section: T282 and S293 Phosphorylationmentioning
confidence: 99%